Evaluasi Penggunaan Sistem Informasi Akademik Al Insyirah (SINAI) menggunakan Pendekatan TAM pada Fakultas Teknologi Kesehatan IKTA - Pratama, Yogi; Andhika, Imam (Innovative: Journal Of Social Science Research, 2025)
Digital transformation in the field of education has encouraged higher education institutions to adopt academic information systems as tools to support administrative activities. This study aims to assess the level of user acceptance and satisfaction regarding the use of the Al Insyirah Academic Information System (SINAI) at the Faculty of Health Technology, Al Insyirah Institute of Health and Technology (IKTA). The study applies the Technology Acceptance Model (TAM) framework, which emphasizes four key variables: perceived usefulness, perceived ease of use, behavioral intention to use, and user satisfaction. This research employs a quantitative approach with a descriptive design. A total of 60 respondents—comprising active students and lecturers—were selected using purposive sampling. Data were collected through questionnaires and analyzed using descriptive statistics. The results indicate that all TAM constructs fall within the high to very high categories. These findings suggest that the SINAI application has been positively received and effectively supports academic processes within the faculty. The study recommends further feature development and continuous evaluation to enhance the system’s performance and adaptability to user needs.